Endogenous Retrovirus ev21 Dose Not Recombine with ALV-J and Induces the Expression of ISGs in the Host - Feng, Min; Tan, Yan; Dai, Manman; Li, Yuanfang; Xie, Tingting; Li, Hongmei; Shi, Meiqing; Zhang, Xiquan (Frontiers in Cellular and Infection Microbiology, 2016)
Avian leukosis virus subgroup J (ALV-J) infection can cause tumors and immunosuppression. Endogenous viruses integrate into host genomes and can recombine with exogenous avian leukosis virus (ALV). In this study, we analyzed the interaction of endogenous retrovirus 21 (ev21) with the ALV-J in late-feathering Chinese yellow chicken. Two ALV-J strains M180 and K243 were isolated from late-feathering and fast-feathering Chinese yellow chicken flocks, respectively. The env gene of the two strains showed 94.2–94.8% nucleotide identity with reference ALV-J strains. Compared with the env gene and the LTR of ev21 and M180, the nucleotide identity of LTR was 69.7% and env gene was 58.4%, respectively, especially the amino acid identity of env gene as low as 14.2%. Phylogenetic analysis of the nucleotide sequence of the env gene and the 3′LTR showed that M180 was closely related to ALV-J, and was located in a distinct group with ev21 in the phylogenetic tree. Using co-immunoprecipitation (co-IP), we next demonstrate that the envelope protein of ev21 does not interact with the M180 envelope protein. We further show that the envelope protein of ev21 cannot activate ALV-J LTR promoter activity using luciferase-reporter assays. qPCR and western blot analysis revealed that envelope protein of endogenous ev21 can facilitate the expression of PKR at 6h post ALV-J infection (hpi) and facilitate the expression of ISG12 and CH25H at 24 hpi. However, the expression of the env gene of M180 strain was not significantly at 6 and 24 hpi. We conclude that there is no evidence of recombination between endogenous retrovirus ev21 and ALV-J strain M180 in late-feathering Chinese yellow chicken, and envelope protein of ev21 can affect the expression of host ISGs, but appears not to influence the replication of ALV-J strain M180. This is the first report of interaction among the endogenous retrovirus ev21, ALV-J and the late-feathering chicken.